2017
DOI: 10.1016/j.culher.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

User-driven energy efficiency in historic buildings: A review

Abstract: The paper draws from the general literature on energy efficiency and historic buildings to explain the importance and potential of user-driven energy efficiency in historic buildings. It is the first review that places the user as a central object of study in the research field of historic buildings and energy Highlights:• State of the art review on user-driven energy efficiency in historic buildings.• Non-intrusive energy efficiency measures have significant impact and potential.• Integrated bottom-up refurbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 40 publications
(17 reference statements)
0
38
0
Order By: Relevance
“…There are not only material aspects to consider when retrofitting historical buildings. Users' behaviour has an important role to play in mitigating climate change, as it determines the preference and choice for room temperature and ventilation, for instance [38], and can help target specific groups in carbon reduction strategies. Many studies highlighted the high energy saving potential derived from changes in user behaviour [39][40][41][42][43], which they estimated to range from 62 to 86% [40].…”
Section: Mitigating Climate Change In the Cultural Built Heritage Sectormentioning
confidence: 99%
“…There are not only material aspects to consider when retrofitting historical buildings. Users' behaviour has an important role to play in mitigating climate change, as it determines the preference and choice for room temperature and ventilation, for instance [38], and can help target specific groups in carbon reduction strategies. Many studies highlighted the high energy saving potential derived from changes in user behaviour [39][40][41][42][43], which they estimated to range from 62 to 86% [40].…”
Section: Mitigating Climate Change In the Cultural Built Heritage Sectormentioning
confidence: 99%
“…The investigation of how users can implement non-intrusive energy efficiency measures in historic buildings was in particular focus. 13 A historic apartment building in a conservation area of Oslo was used as a case study for both technical surveys and interviews with owners and residents. The apartment building is a representative example of its time and consists of two buildings, one in front facing the street and one in the back.…”
Section: Project Backgroundsmentioning
confidence: 99%
“…Fouseki and Cassar 31 stated that 'studies of occupants' attitudes and behaviour with regard to energy-efficiency interventions are critical' when they addressed the topic and future research needs in their 2014 editorial. Berg et al 32 further concluded that residents represent an important resource that can foster lower energy demand and less intrusive interventions in historic buildings provided that they are included in the planning and follow-up phase of the refurbishment process.…”
Section: Resident Motivation and Energy Renovationmentioning
confidence: 99%
“…Over the last decade, the need for adaptation, upgrading, and energy efficiency of historic buildings has been recognized as a key-theme in the debate for the definition of a new paradigm of sustainable development. In this sense, activities aimed at the revitalization and energyarchitectural upgrading of historic buildings with a high artistic and cultural value have raised great interest in the scientific community [1][2][3]. In particular, Italy, which represents the first country in the world for the number of UNESCO World Heritage Sites [4], is an excellent "laboratory" for the study and development of new restoration techniques able to combine conservation and energy efficiency.…”
Section: Introductionmentioning
confidence: 99%